2015
DOI: 10.1590/1981-7746-sip00083
|View full text |Cite
|
Sign up to set email alerts
|

Concepções E Práticas Dos Profissionais De Saúde Acerca Da Violência Intrafamiliar Contra Crianças E Adolescentes

Abstract: Resumo Estudo qualitativo com profissionais da Estratégia Saúde da Família, a fim de investigar suas concepções e práticas acerca da violência intrafamiliar contra crianças e adolescentes. A coleta de dados foi realizada no período de abril a julho de 2014, por meio de entrevista semiestruturada, realizada em Unidades Integradas de Saúde da Família em João Pessoa, Paraíba. A análise temática evidenciou que profissionais de saúde mostram-se inseguros e despreparados para lidar com a violência intrafamiliar cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0
20

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 15 publications
(8 reference statements)
0
3
0
20
Order By: Relevance
“…Violence is a multifaceted problem associated with economic and social inequality, cultural factors, and the distinctive subjective and behavioral characteristics of different societies [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Violence is a multifaceted problem associated with economic and social inequality, cultural factors, and the distinctive subjective and behavioral characteristics of different societies [8][9][10] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the continuous monitoring of external causes and violence against adolescents is essential for effective policy implementation 14 . However, studies of violence in this age group tend to be qualitative 9,12 , rely on hospital admission and mortality databases 11 , and focus on the local level 13 and, as a result, national studies of violence in this age group remain scarce.…”
Section: Introductionmentioning
confidence: 99%
“…In the reports, it is possible to note that families do not perceive themselves as aggressors, since they believe that punishment is part of the education process of the child. The cases of violence, usually, present themselves with cultural and social normativity 26 , and the family, which should play the role of protecting the child, is one of the main providers of aggression, compromising his/her welfare and the psychosocial performance 7,27,28 .…”
Section: Involvement Of the Family In Situations Of Violence Against mentioning
confidence: 99%
“…O cuidar do sofrer e das subjetividades é desafiador e convoca a equipe a construí-lo conjuntamente com o usuário, a cocriar outras possibilidades de vida COLVERO, 2013;COSTA et al, 2015). De modo que não se trata apenas de curar uma morbidade, circunscrevendo este cuidar ao corpo físico, deve ir além, muito além, deve flertar com a angústia e acolhê-la.…”
Section: O Setor Saúdeunclassified